The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.26872/jmes.2017.8.12.472
|View full text |Cite
|
Sign up to set email alerts
|

Study of reproduction of anchovy Engraulis encrasicolus (Actinopterygii, Engraulidae) in the central area of the Moroccan Atlantic coast

Abstract: Morocco is one of the four regions in the world known for the richness of its fish resources in its coasts (through upwelling). The upwelling phenomenon is the origin of high biological productivity of the regions which results in a strong richness of the pelagic resources (sardines, anchovies, mackerel, etc.). These species were defined as fish living in the sea between the surface and 200 meters deep and characterized by significant horizontal and vertical migration in coastal waters [1]. They make up the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
2
2
0
3
Order By: Relevance
“…This signifies that fishes that belong to the same species may attain first maturity at different sizes depending on the condition of the environments they inhabit and other associated factors. This is in agreement with other scientists who suggested that the growth of fish could be retarded by environmental conditions and food resources (Wootton, 1990) and pressure exerted from fishing activities (Baali et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This signifies that fishes that belong to the same species may attain first maturity at different sizes depending on the condition of the environments they inhabit and other associated factors. This is in agreement with other scientists who suggested that the growth of fish could be retarded by environmental conditions and food resources (Wootton, 1990) and pressure exerted from fishing activities (Baali et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, changes in size at first maturity may be ascribed to the different strategies utilised by fish in different environments to better adapt to environmental conditions (Baali et al, 2017). This study also demonstrated that males of both species attained first sexual maturity at smaller sizes than females.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Antxoaren populazio-dinamika nagusiki errekrutamenduaren mendekoa da, hots, ale helduen multzoari urtero gehitzen zaizkion ale berrien ko-Antxoaren maneiu eta kontserbazioa: biomasan eragiten duten faktoreen azterketa puruaren mendekoa [6]. Antxoak errundako arrautza kopuruaren eta bertatik jaiotako larben kopuruaren eta helduen kopuruaren artean erlazio zuzenik ez egoteak agerian uzten du inguruneak (eragile biotiko eta abiotikoak) fase goiztiarreko heriotza-tasan eragin zuzena duela [7]. Era berean, Aldanondok [8] jakinarazi zuen urteko errekrutamenduan eragin handia izan zezaketen eragileetako bi erreklutamenduari berari loturiko hilkortasuna (arrautzen eta larba goiztiarrena) eta baita aleen neguko hilkortasuna izan zitezkeela.…”
unclassified
“…Edozein animalia helduren egoera biologikoan, erreserba energetikoek berebiziko garrantzia dute. Zenbat eta erreserba energetiko gehiago izan animaliak, orduan eta egoera biologiko hobea izango du; izan ere, erreserba energetiko nahikoa ez izateak baldintza kaskarreko egoerei aurre egiteko aukerak murrizten ditu [9]. Hots, indibiduo batek oinarrizko funtzioak betetzeko adina energia badu soilik, oinarrizko funtzio horiek aldatzen dituen edozein ingurune-baldintzak indibiduo horren heriotza ekar lezake.…”
unclassified